A history of economic theory and method - Ekelund, Robert B.; Hébert, Robert F. (New York : McGraw-Hill, 1975)
The book covers economic ideas from ancient times to the present, this outstanding text presents to the student powerful insight into the broad scope of past intellectual contributions to the evolution of contemporary economic thinking. Notably shying from a mind-numbing encyclopedic listing of isolated people and dusty ideas, the authors provide engaging discourse of both the ideas which have shaped contemporary economic theory and the different methods used for problem solving.
Includes bibliographies and indexes.
rpm 05/10/2017
Loans
Keywords: Economics; Economic theory; Economic method